Quality assurance and its impact from higher education institutions’ perspectives: Sequential Explanatory Strategies for Alumni - Irawati Sabban; Irfan Hi. Abd Rahman (Record and Library Journal, 2022)
Background of the study: The implementation of quality assurance at Morotai Pacific University does not improve and improve the quality of higher education implementation in the Border Area of Morotai Island Regency. This is evidenced by until now the University of the Pacific Morotai does not have university accreditation. Purpose: This research aims to find objective, accountable evidence in helping universities make improvements in developing quality universities and improve strategies in carrying out quality assurance at the college. Method: This research uses mixed methods with sequential explanatory strategies implemented of alumni at the Morotai Pacific University of North Maluku as the Border Region of the Republic of Indonesia. Findings: The results showed that there are still many graduates of pacific morotai universities who do not have a job, and are looking for work. While the perspective of alumni on ability in the academic field is focused on aspects of graduates who have special competencies, general competence, personality competence, and infrastructure. The addition of teaching staff is also one of the concerns of alumni to meet the ratio of lecturers to students. Conclusion: This article defines the essence of the parameters and dimensions of quality assurance of universities in Indonesia, especially at the Morotai Pacific University in North Maluku through the application of quality assurance models.